Misconception about photosynthesis and respiration held by grade 11 and 12 biology learners in Onathinge circuit in Namibia. - Uunona, Tseline (Midlands State University, 2017)
The study sought to investigate the misconception about photosynthesis and respiration held by Grade 11 and 12 Biology learners in Onathinge circuit in Namibia. The research employed the descriptive survey design. Data was gathered through the uses of tests, observations and interviews. The population was made up of 4 secondary schools, 80 learners and 4 Biology teachers. The sample consists of 80 learners 20 from each school and 4 Biology teachers 1 per school. The researcher used random simple sampling in selecting 1 teacher from each school, by the drawing the names of the teachers in a box. The study involved both Grade 11 and 12 students in the secondary school. Stratified random sampling was employed for selecting 20 learners per school each acted as a strata. Simple random sampling was employed whereby names was drawn from a box and 10 was selected from each grade,10 from Grade 11 and another 10 from Grade 12, make them 20 learners per school and in all 4 secondary school make the 80 (eighty) students. Data were presented in a table form and interpreted. During data analysis, the frequencies of correct responses, incorrect responses because of misconceptions, incorrect responses for lack of evidence of understanding and response items was noted for each item. Percentages of the responds in each category were calculated too. Qualitative data obtained through interviews was summarized and analyses by interpretation. Descriptive statistical analyses quantitative data, it was found that majority of the students had misconceptions about photosynthesis and respiration. The misconception identified was that photosynthesis and respiration are functioning in an opposite and contrasting manner. Learners held misconception that plants photosynthesis during the day, where as they respire at night, another held this misconception that only animals need oxygen for them to survive and more students held misconception that plant photosynthesis, whereas animal respire and many more other misconception. Findings from the study reveal that the terms and explanation used by teachers, presentations of concepts in textbooks and ineffective communication between students and teachers are the cause of students’ misconceptions. However it was found that these misconceptions can be minimized or dealt with by use of the conceptual change model when teaching. Recommendations made were that graduating teachers should be well equipped with the various strategies for teaching skills in sciences so as to improve teaching and learning in the subject.